Neuropeptide W - Takenoya, Fumiko; Kageyama, Haruaki; Hirako, Satoshi; Ota, Eiji; Ogawa, Tetsuo; Wada, Nobuhiro; Ryushi, Tomoo; Shioda, Seiji (Frontiers in Endocrinology, 2012)
Neuropeptide W (NPW), which was first isolated from the porcine hypothalamus, exists in two forms, consisting of 23 (NPW23) or 30 (NPW30) amino acids. These neuropeptides bind to one of two neuropeptide W receptors, either NPBWR1 (otherwise known as GPR7) or NPBWR2 (GPR8), which belong to the G protein-coupled receptor family. GPR7 is expressed in the brain and peripheral organs of both humans and rodents, whereas GPR8 is not found in rodents. GPR7 mRNA in rodents is widely expressed in several hypothalamic regions, including the paraventricular, supraoptic, ventromedial, dorsomedial, suprachiasmatic and arcuate nuclei. These observations suggest that GPR7 plays a crucial role in the modulation of neuroendocrine function. The intracerebroventricular infusion of NPW has been shown to suppress food intake and body weight and to increase both heat production and body temperature, suggesting that this neuropeptide functions as an endogenous catabolic signaling molecule. Here we summarize our current understanding of the distribution and function of NPW in the brain.